Synthesis and characterization of novel tricarboxylatoplatinum(IV) complexes. Nucleophilic substitution of (diamine)-tetrahydroxoplatinum(IV) with carboxylic acid - Song, R; Kim, KM; Sohn, YS (ELSEVIER SCIENCE SA, 2002)
The reaction of [Pt(IV)(dach)(OH)(4)] (dach = trans-(+/-)-1,2-diaminocyclohexane) with an excess of carboxylic acid at room temperature afforded tricarboxylatoplatinum(IV) complexes, [Pt(dach)(L)3(OH)] (L = acetato, propionato, valerato) in contrast to the carboxylation reaction with excess carboxylic anhydrides, which gave only tetracarboxylatoplatinum(IV) complexes as a major product. The protonation on hydroxo ligand of the platinum(IV) complex to form aqua ligand seems to be followed by nucleophilic substitution by carboxylate or chloride anion. Such nucleophilic substitution afforded only partially substituted tricarboxylatoplatinum(IV) complexes in carboxylic acid solvent whereas the reaction in 0.1 M HCl solution gave tetrachloroplatinum(IV) complex. This difference is explainable by different pK(a) values of the four aqua ligands, among which the last aqua ligand may have sufficiently low pK(a) value allowing the protonation only in strong acidic media like hydrochloric acid. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: PLATINUM(IV) COMPLEXES; ANTITUMOR; REDUCTION; CISPLATIN; KINETICS; ISOMERS; CRYSTAL